PENGUATAN PRODUK TAS TANGGULANGIN SIDOARJO - Ronny, Ronny; Sihotang, Ellen Theresia; Sekarsari, Larasati Ayu (Pusat Penelitian dan Pengabdian Kepada Masyarakat (P2M) IKIP Budi Utomo Malang, 2018)
The purpose of this public service program is to empower the Kartika Utama SMEs and Schonheit Goods SMEs as SMEs that partner with each other in marketing bag products. Kartika Utama SMEs as an SMEs that produces bags, while Schonheit Goods SMEs as an SMEs that markets bag products from Kartika Utama SMEs. The problems faced by these two SMEs are related to file archiving, product packaging, and production that still need to be improved, as well as opportunities, to utilize the internet in the framework of better marketing. The method of implementing this public service program is training, mentoring SMEs, and creating websites to market bag products produced. The results of dedication to strengthening SMEs in two fields, namely production and marketing with emphasis on online marketing.